Physiological Roles of GPR10 and PrRP Signaling - Dodd, Garron T.; Luckman, Simon M. (Frontiers in Endocrinology, 2013)
Prolactin-releasing peptide (PrRP) was first isolated from bovine hypothalamus, and was found to act as an endogenous ligand at the G-protein-coupled receptor 10 (GPR10 or hGR3). Although originally named as it can affect the secretion of prolactin from anterior pituitary cells, the potential functions for this peptide have been greatly expanded over the past decade. Anatomical, pharmacological and physiological studies indicate that PrRP, signalling via the GPR10 receptor, may have a wide range of roles in neuroendocrinology; such as in energy homeostasis, stress responses, cardiovascular regulation and circadian function. This review will provide the current knowledge of the PrRP and GPR10 signalling system, its putative functions, implications for therapy and future perspectives.